Urban clustering and residential concentration pattern assessment in a GIS environment. Application to the Region of Thessaly, Greece. - Stelios Tsompanolgou; Yorgos Photis (European Regional Science Association (ERSA), 2004)
The main aim of this paper is the definition of a methodological framework for the determination, analysis and cross-evaluation of urban clusters which are formulated within wider study areas, such as administrative regions. To this end, different methods and techniques are utilised, that stem from the fields of Statistics and Quantitative Spatial Analysis and which during the last years are all the more commonly applied to the different stages of Geographical Analysis. In this regard, the four interconnecting components that form the proposed methodology are Cluster Analysis, Distance Counts, Location Quotient and Nearest Neighbour Analysis along with the analytical and presentational capabilities of G.I.S. technology. The definition of urban clusters is mainly based on different types of variables such as the demographic characteristics of the cities, the number of public facilities located in them, as well as the total length of the different types of road network in the study area. At its final state, the proposed methodological approach is strengthened by the formulation of a comparative indicator of spatial concentration reflecting the role and the relative weight of every urban area in the study region as well as its spatial influence. Such a metric, improves the definition and analysis of urban clusters and in the same time, constitutes an alternative assessment of their overall locational perspective. Both the proposed methodological framework and the formulated indicator are applied and in the region of Thessaly, Greece.
Keywords: 330